A conjunctural analysis of the origins of ‘embedded ELSI’ in U.S. genomic medicine - James Karabin; Chessa Adsit-Morris; Sandra Soo-Jin Lee; Stephanie M. Fullerton; Mildred K. Cho; Jenny Reardon (Journal of Responsible Innovation)
Calls to identify, explore, and address ethical and social issues as part of the design and implementation of scientific research are now widespread. One way of doing so is through an embedded approach, where ethical, legal, and social implications (ELSI) researchers are situated within larger scientific research studies. We trace the emergence of the ‘embedded ELSI’ approach to integration alongside the development of genomic medicine. In particular, we conduct a conjunctural analysis that draws attention to contests and struggles over the forms and meanings of good science – in this case, genomics – and the role(s) of ELSI scholars and researchers in producing good science. We demonstrate that the embedded ELSI approach emerged from these contests, which left ELSI research and interventions constrained – institutionally, topically, and methodologically. We end by calling for an opening up of embedded approaches to integration so that they might better meet calls for justice and equity in the present conjuncture.